2005
DOI: 10.1532/lh96.04049
|View full text |Cite
|
Sign up to set email alerts
|

Anemia of Chronic Disease: Pathophysiology and Laboratory Diagnosis

Abstract: Classic iron deficiency (ID) does not represent a challenge for the laboratory and physicians. The anemia that accompanies infection, inflammation, and cancer, commonly termed anemia of chronic disease (ACD), features apparently normal or increased iron stores. However, 20% of these patients have iron-restricted erythropoiesis (functional ID), an imbalance between the iron requirements of the erythroid marrow and the actual iron supply. Functional ID leads to a reduction in red cell hemoglobiniza-tion, causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 40 publications
1
68
1
12
Order By: Relevance
“…Portillo et al 13 reported most patients with chronic disease in Spain have normocytic normochromic anemia, while Thomas et al 14 stated that iron deficiency causes microcytic hypochromic anemia to patients in Germany. 13,14 Nevertheless, it is not uncommon for anemia in SLE to manifest due to both chronic disease and IDA simultaneously. 5 This study also revealed that most subjects had either moderate anemia (50%) or mild anemia (42%).…”
Section: Discussionmentioning
confidence: 99%
“…Portillo et al 13 reported most patients with chronic disease in Spain have normocytic normochromic anemia, while Thomas et al 14 stated that iron deficiency causes microcytic hypochromic anemia to patients in Germany. 13,14 Nevertheless, it is not uncommon for anemia in SLE to manifest due to both chronic disease and IDA simultaneously. 5 This study also revealed that most subjects had either moderate anemia (50%) or mild anemia (42%).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish between ACD and ACD/IDA to appropriately guide therapeutic regimens, especially in respect to iron repletion strategies. 7,27 We used a rat model of inflammation-associated chronic anemia to investigate the regulation of body iron homeostasis in ACD. We observed increased expression of the iron storage protein ferritin in the spleen but not in the liver, a finding in accordance with previous data demonstrating divergent ferroportin regulation by hepcidin in duodenum and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Tómasartaflan hefur þann kost að geta greint á milli starfraens járnskorts, það er ófullnaegjandi framboðs á járni til rauðkornskímfrumna þó að járnbirgðir séu naegar, og raunverulegs járnskorts og hún getur komið að gagni við val á meðferð við blóðleysi og við mat á árangri af þeirri meðferð. [6][7][8] CHr laekkar við járnskort eins og MCV en mun hraðar og eykst aftur í eðlilegt gildi á örfáum dögum þegar rauðkornskímfrumurnar fá aftur naegt járn. 9 sTfRferritín-vísir hefur verið talinn betri maelikvarði á járnhag en sTfR.…”
Section: Inngangurunclassified
“…[6][7][8] Árangur af járngjöf getur komið fram í því að CHr eykst og/eða að sTfRferritín-vísir laekkar þannig að hnit sjúklingsins hliðrast upp á við og/eða til vinsri á mynd 1, jafnvel á milli flokka og flytjast þá í flokk með haerra CHr eða laegri sTfR-ferritín-vísi. Ef hnit sjúklings sem faer epóetín hliðrast í gagnstaeða átt getur það bent til þess að starfraenn járnskortur sé til staðar og þá gaeti betri árangur fengist með því að auka járngjöf eða baeta henni við meðferðina.…”
Section: Umraeðaunclassified
See 1 more Smart Citation